Tyrant and Penitent: Nebuchadnezzar and Biblical Exemplarity - Wiseman, Jake (Reformation, 2024)
At the end of the fourth chapter of the Book of Daniel, the Babylonian king Nebuchadnezzar is punished for his pride. He is cast out from his kingdom, forced to eat grass with wild beasts, and repents before being restored to his throne. This article examines the encounters between this ancient biblical narrative, humanist rhetoric of exemplarity, and reformed doctrines of repentance. Nebuchadnezzar’s narrative tested the capacity of exemplarity to absorb singular biblical texts into reformed theologies. Exemplarity offered John Calvin a rhetorical tool with which to refashion Nebuchadnezzar as a model of reformed penitential doctrine. The article shows that the popular preacher Henry Smith (c. 1560–91) read Calvin’s lectures on Daniel, and applied Nebuchadnezzar’s example to the lives of his Elizabethan congregants. Annotations and a manuscript notebook reveal that readers turned to Smith’s sermons for the extractable moral and spiritual lessons carried by Nebuchadnezzar’s exemplary narrative.